DETERMINAN SEWA ANJUNGAN TUNAI MANDIRI (ATM) DI LINGKUNGAN KAMPUS UGM YOGYAKARTA - , Ahmad Endang D Hidayat; , Dr. Soeratno. M.Ec. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aimed to identify the determinants of rental value ATM space rent in University of Gadjah Mada Yogyakarta and compile them in a rental ATM space rent valuation models. The reasearch used cross section data obtained by observing 13 scattered object in various locations in University of Gadjah Mada Yogyakarta. Secondary data such as ATM space rent, student, teacher and employe population, and also âzoning dan klaster fakultasâ derived from Rektorat UGM and relevant fakulties. Multiple linear regression analysis with Ordinary Least Square method were used to measure the influence of the determinant such potensial user, distance from a public road, the distance from the security post, spacious room for rent, dummy form of the agreement and the ontract period to rent space ATM. Log-log model was chosen as the best estimation model with coefficient of determination (R2) was about 96,72 percent which means that the 96,72 percent behavior of the dependent variable was able to be explained by the independentn variables. Test results of economics, statistics and econometrics indicate that the number of potential users, the distance to a public road, and spacious is rented, have a significant effect while the distance to the nearest post, the agreement, and the contract period does not significantly affect the value of rental space ATM. Keywords: The rental value of space ATM, Multiple linear regression analysis